2009
DOI: 10.1111/j.1440-1843.2009.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ‘atypical pathogens’ among adult hospitalized patients with community‐acquired pneumonia

Abstract: ABSTRACT; non-invasive ventilation 3.7% vs 3.3%; admission to the intensive care unit 4.5% vs 2.7%; length of hospitalization 6 day vs 7 day; 30-day mortality: 2.2% vs 6.0%; overall P > 0.05). Age <65 years, female gender, fever Ն38.0°C, respiratory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
51
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 42 publications
13
51
3
1
Order By: Relevance
“…Several genera of important possible pathogens were detected by the 454 platform but were absent from the list obtained by the clinical method. According to our knowledge and published articles, Mycoplasma, Haemophilus, and Moraxella are referred to as atypical pathogens of pneumonia [5,[26][27][28]. Compared with clinical reports, these potential pathogens were only found sporadically by our method in sputum samples.…”
Section: This Indicates That Althoughmentioning
confidence: 88%
“…Several genera of important possible pathogens were detected by the 454 platform but were absent from the list obtained by the clinical method. According to our knowledge and published articles, Mycoplasma, Haemophilus, and Moraxella are referred to as atypical pathogens of pneumonia [5,[26][27][28]. Compared with clinical reports, these potential pathogens were only found sporadically by our method in sputum samples.…”
Section: This Indicates That Althoughmentioning
confidence: 88%
“…In China, viral pathogens were identified as adenovirus, influenza virus B, respiratory syncytial virus and influenza virus A in 16, 12, 3 and 5 CAP patients, respectively [44]. In Hong Kong, viral pathogens were identified in 126 (10.6%) of 1193 CAP patients, including influenza virus in 8.5% [60].…”
Section: Endemic Community-acquired Pneumonia Pathogensmentioning
confidence: 99%
“…In Hong Kong, a single-centre prospective observational study was conducted in adults admitted to hospital over an 18-month period in 2004-2005 [60]. Of the patients with aetiological diagnoses, 28.6% had infections with atypical pathogens.…”
Section: Pathogenmentioning
confidence: 99%
“…The study by Arnold et al [16] showed that the incidence of CAP due C. pneumoniae from 4337 patients was 8 % in North America, 7 % in Europe, 6 % in Latin America, and 5 % in Asia. Lui et al [37], in a prospective observational study of hospitalized patients with CAP, reported that 29 % of cases with defined etiology were caused by intracellular pathogens; of these, 35 % were classified as PSI IV-V, 5 % of these cases needed ICU admission, and the mortality rate was 2.2 % in the atypical group. A study from Thailand on severe CAP reported that the incidence of C. pneumoniae pneumonias was 3-23 cases per 100,000 population; the highest rates were among patients aged under 1 year (18-166 cases per 100,000) and those aged 70 years or over (23-201 cases per 100,000) [38].…”
Section: Chlamydophila Pneumoniae and Chlamydophila Psittacimentioning
confidence: 99%